Use of lumbar point for the estimation of potential and kinetic mechanical power in running - Slawinski, J.; Billat, V.; Koralsztein, J. P.; Tavernier, M. (Journal of Applied Biomechanics, 2004)
The purpose of this study was to estimate the difference between potential and kinetic mechanical powers in running (Pke, Ppe) calculated from the center of mass and one anatomic point of the body located on the lower part of the runner`s back, the"lumbar point." Six runners undertook a treadmill run at constant velocity and were filmed individually with a video camera (25 Hz). The 3-D motion analysis system, ANIMAN3D, uses a numerical manikin (MAN3D) which compares a voluminal subject (the athlete) directly to the manikin which possesses the same voluminal properties. This analysis system allows the trajectories of the center of mass and the lumbar point to be calculated. Then, from these trajectories, potential and kinetic mechanical powers in running are calculated. The results show that the utilization of the lumbar point rather than the runner`s center of mass leads to a significant overestimation of Pke and a significant underestimation of Ppe (both p < 0.05). In spite of these differences, however, both methods of calculating Pke and Ppe are well correlated: respectively, r = 0.92; p £ 0.01, and r = 0.68; p £ 0.05. Taking into account that the trajectory of an anatomic point is experimentally easier to access than that of the center of mass, such a point could be used to estimate the evolution of kinetic or potential energy variation in different cases. However, when the lumbar point rather than the center of mass is used to estimate the mechanical energy produced in running, Pke could appear to be a discriminating parameter, which it is not.